KAJIAN ATAS PERTANGGUNGJAWABAN PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH HEWAN BERDASARKAN HUKUM INDONESIA DAN HUKUM JERMAN - Gratianus Prikasetya Putra (President University, 2016)
There are 2 (two) forms of liabilities which acknowledged by Civil Law, the first one is contractual based liability and the second one is tort based liability. If there is a liabilty that based on an event which fulfill the elements that known in tort theory, so the tort based liability will be used. Today, there are some variations and development in cases that intersects with the theory and regulation regarding tort. One of the case which related to that theory and regulation was the tort that has been done by an animal in Germany. According to the case it can be seen the possibilitiy of tort based liability that owned by an animal. This article will explain regarding the tort theory and the liablity based on both Civil Law System in Indonesia and Germany by doing the comparison on it. The Comparison will consist of regulation and theory comparison regarding the tort which aplicable both in Indonesia and Germany.